Dall'empiriocriticismo al positivismo relativistico Joseph Petzoldt tra l'eredità di Mach e Avenarius e il confronto con la relatività einsteiniana - Chiara Russo Krauss (Scuola delle Scienze Umane e Sociali. Quaderni, 2020)
Joseph Petzoldt was Ernst Mach's and Richard Avenarius' main pupil, as well as the primary source for the habit to reunite these two thinkers under the label of "empiriocriticists". Petzoldt developed Mach's and Avenarius' ideas in a philosophical system aiming at overcoming the dualism and agnosticism of the Kantian approach that was typical of German scientific circles in the late 1800s. Petzoldt's thought is based on three pillars: his radical empiricism, according to which sensory experience is not appearance but reality; the Eindeutigkeit principle, which states that all that happens is univocally determined and thus necessary; the principle of the tendency to stability, which governs the evolution of the universe, including the living organisms and the brain. On these bases, Petzoldt arrives at his "relativistic positivism", according to which every individual experiences reality from his point of view, but - since knowledge processes are determined by the functioning of the brain - this does not preclude an objective knowledge of the world. Petzoldt was also one of the leading figures of the debate on the philosophical interpretation of Einstein's relativity. He believed that relativity was a consequence and a confirmation of E. Mach gnoseological approach and thus of relativistic positivism.